IMPLEMENTASI IMPERATIF KATEGORIS DALAM SISTEM PENDIDIKAN - Widyawati, Setya (Acintya, 2016)
This study entitled The Implementation Categorical Imperatives in The Education System aims to determine the ethical thinking of Immanuel Kant, his inference, as well as its implementation in learning. This is a literature study using axiological approach in the branch of ethics. The material object is the implementation of ethical thinking into learning while the formal object is axiological philosophy. Immanuel Kant was a German philosopher (1724-1804) who suggested that the first argument of morality is to have true oral values. Deeds needed to be done in terms of liability. The second proposition is an act done out of obligation that does not have the moral objectives to be achieved through but in the doctrine in which it is determined. Therefore, the moral value does not depend on the realization of the object but only works on the principle of volition by which the act is done without regard to the objects of basic skills. The government’s policy in shaping characters is done gradually starting in 2004 with Kurikulum Berbasis Kompetensi (KBK; Competency-based Curriculum). At 2011, the government issued Kurikulum Pendidikan Karakter (Character Education Curriculum).The most actual policy for higher education was issued in 2013 entitled Standar Nasional Pendidikan Tinggi (SNPT; National Standard of Higher Education) referring to Kerangka Kualifikasi Nasional Indonesia (KKNI; National Framework’s Qualification of Indonesia). Learning is one of the objects in the education system. Art education system is a unique educational system because it accentuates the value of ethnic cultural heritage as part of the national identity. Relevance between Immanuel Kant’s categorical imperative with the world of education lies in the role of the categorical imperative thatinspires people to realize the importance of good will unconditionally. Internal awareness of inherent is a soft skill so as to contribute in the education world. In turn, education will produce quality output that is sought after by the world of work.Keywords: ethics, curriculum, learning, educational system, the categorical imperative.